تطوير الخطات التدريس على طريقة الحركية في تعليم مهارة الكلام بمدرسة العالية الحكومية الأولى موجوكرطا - Muqimah Liwais Sunnah; Abdulloh Sattar (Dirosatuna: Journal of Islamic Studies, 2021)
Speaking’s skill is essential in learning of Arabic language. Speaking could describe a student’s ability in the Arabic language. The title of this research is Development Of Learning Implementation Plans By Using Kinesthetic Method In Speaking X Class Of MAN 1 Mojokerto. The formulation of this research problem is (1) Why does the Arabic-speaking learning method in X class of MAN 1 Mojokerto needs development? (2) How does specification development of the kinesthetic method in learning to speak Arabic for X-class students of MAN 1 Mojokerto needs development? Furthermore, the background of this research because many students find it challenging to speak Arabic because little vocabulary, practice, and methods are used.The research method used is research and development (R&D). Product that developed is learning implementation plans using kinesthetic method, title of material used is المعرض، الحياة في الأسرة، في الصفّ، هواية الطلاب، في مكتبة الفصل، المرافق العامة في المدرسة، البيانات الشخصية، المهنة والحيا. The kinesthetic method is the movement of the part body when speaking that describes something that is said.To determine the feasibility of the product developed, the reacherser took data from two validators with a questionnaire, the score from first validator 70%, score from second validator was 65%, and the average value from the two validators was 67,5. Based on assessment criteria, the average value is categorized as valid and usable but needs a little revision.